United Kingdom : Financial Sector Assessment Program-Financial Stability and Managing Institutional, Technology, and Market Transitions. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
There has been a very smooth post-Brexit transition, with no material disruption nor any crystalized financial stability risks. This was the result of the U.K. authorities' (and in some cases the EU authorities) and firms' extensive preparations. The U.K. authorities have been proactively engaging with the industry, monitored risks, and consistently provided necessary legal certainty in a timely manner. This approach should continue, to the extent that any risks and uncertainties from Brexit remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy